2013
DOI: 10.2460/ajvr.74.11.1450
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, bioavailability, and hemodynamic effects of trazodone after intravenous and oral administration of a single dose to dogs

Abstract: Results of this study indicated oral administration of trazodone resulted in acceptable absolute bioavailability, with substantial variability in time to maximum plasma concentration. Individualized approaches in dosing intervals may be necessary for dogs receiving oral trazodone. An orally administered dose of 8 mg/kg was well tolerated in dogs; IV administration of a dose of 8 mg/kg caused substantial adverse effects, including tachycardia and behavior disinhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 20 publications
3
74
1
1
Order By: Relevance
“…8 A pharmacokinetic study of single-dose oral trazodone in dogs revealed an elimination half-life of 166 ± 47 minutes. 13 In the present study, cases in which the duration of action seemed insufficient, on an individual basis the trazodone dose schedule was increased to three times daily.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…8 A pharmacokinetic study of single-dose oral trazodone in dogs revealed an elimination half-life of 166 ± 47 minutes. 13 In the present study, cases in which the duration of action seemed insufficient, on an individual basis the trazodone dose schedule was increased to three times daily.…”
Section: Discussionmentioning
confidence: 72%
“…A recent single dose pharmacokinetic study of trazodone in six dogs, found that when given orally, trazodone produced mild sedation with no observable side effects. 13 In anesthetized dogs, trazodone has been shown to have very little effect on cardiac function, compared with equally effective dosages of imipramine. 14 These characteristics make trazodone an ideal agent to decrease anxiety, agitation, and distress associated with confinement in post-surgical dogs.…”
Section: Introductionmentioning
confidence: 99%
“…The actual extent of absorption could not be determined due to the lack of an intravenous dose. Intravenous dosing was not performed due to the unacceptable level of adverse effects noted in dogs and horses, including tachycardia, aggression/excitation and whole body tremors (Jay et al., ; Knych et al., ). This, in addition to the lack of a commercially available injectable formulation, makes intravenous dosing unlikely to be clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…A linear relationship existed between plasma concentrations and sedation and ataxia scores at the 10 mg/kg dose where oversedation was noted in three of six horses. Behavioural calming effects in dogs are seen at concentrations between 0.13 and 2 μg/ml (Jay et al., ). A threshold concentration of 0.7 μg/ml has been described for humans being treated for major depressive order (Mihara et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…One study of trazodone in conscious dogs found six of six greyhounds developed a transient tachycardia following intravenous administration of 8 mg/kg trazodone and three of the six developed signs of aggression. An oral dose of 8 mg/kg had no such adverse effects (Jay and others 2013). However, no significant increases in heart rate (HR) were reported in pentobarbital-anaesthetised dogs receiving up to 30 mg/kg trazodone (Gomoll and others 1979).…”
Section: Discussionmentioning
confidence: 99%